FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PENYALURAN KREDIT PERBANKAN KONVENSIONAL BEI 2018-2021 - Puji Rahayu, Puji Rahayu; Safrizal, Safrizal; Masril, Masril (Journal of Management and Business, 2023)
This study aims to determine the effect of demand deposits, savings and time deposits on the amount of credit extended to banking sub-sector companies listed on the Indonesia Stock Exchange. The subjects of this research were banking sub-sector companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The population in this study were all banking companies listed on the IDX, and with a total sample of 26 companies with a four-year study period, using a purposive sampling technique. Data analysis techniques using multiple linear regression. The results of the analysis show that demand deposits have no effect on the amount of lending, while savings have an effect and are significant on the amount of lending, and deposits have a significant effect on the amount of lending.